The Benefits of Probiotics on Oral Health: Systematic Review of the Literature - Francesco Inchingolo; Angelo Michele Inchingolo; Giuseppina Malcangi; Nicole De Leonardis; Roberta Sardano; Carmela Pezzolla; Elisabetta de Ruvo; Daniela Di Venere; Andrea Palermo; Alessio Danilo Inchingolo; Alberto Corriero; Gianna Dipalma (MDPI AG, 2023)
Aim: Probiotic microorganisms, commonly used to bolster gut health, might also have benefits for dental health, according to certain studies. Probiotics (PBs) are associated with reducing cariogenic pathogens and protecting against periodontal diseases, although the exact way they function in the mouth is not fully clear. Our study aimed to explore the use of PBs to improve oral health, focusing on issues such as cavities, gum disease, bad breath, mucositis, and periimplantitis. Materials and Methods: We utilized the Boolean keywords "Probiotics" AND "Oral health" to search the databases of PubMed, Scopus, and Web of Science. The search was restricted to English-language papers published from 1 January 2019 to 13 April 2023. Results: A total of 3460 articles were found through our computerized search. After removing duplicates, reviewing the papers, and determining their relevance, 12 were selected for inclusion. Conclusions: Assessing how bacteria in food or dietary supplements might alter the stable oral microbiota is a complex task. Although probiotic microorganisms have been found to have proven therapeutic benefits, their application in dental health is not yet solidly backed by evidence. Further research is necessary to thoroughly understand the long-term effects of probiotic bacteria on the oral environment, including their ability to colonize and form biofilms.